O entrelaçamento da mídia com o espetáculo - Bibini, Adriana Barilari (2022)
This research corresponds to the analysis of photographic representations of President Dilma Rousseff during the period of impeachment published by the traditional media Estado de S. Paulo and Folha de S.Paulo. The objective was analyzing the published images and how the narratives about gender are expressed in the photographic representations of Dilma Rousseff, we seek to understand the construction of stereotypes about her political image during the impeachment process and how these helped in the negative image construction of the president. Our hypothesis was that the photographs contained semiotic techniques and photographic compositions capable of arousing affections linked to common sense about women in politics and in public spaces of power. The research analysis made clear the consequences that Dilma Rousseff suffered for challenging traditional gender roles. The symbolic violence she suffered and the negative image of it that was published when she held the most important position in the executive power will mark the history of Brazil as a massive media retaliation